Demographic and Clinicopathological characteristics of breast cancer patients, Baghdad, Iraq - Venus M.Fadil,; Mohsin A. A. Sahib,; Al Khaldy, Najim; Al-Rufaee, Farah L. R.; 5Jawad K.Al-Diwan, (International Journal of Psychosocial Rehabilitation, 2020)
Background: Breast cancer is the most common cancer affecting women all over the world. Breast cancer is the most frequent cancer among women in Iraq. Objectives: to highlight the main demographic characteristics and clinicopathological characteristics of female patients registered with breast cancer in Iraq. Method: A retrospective study done on 264 diagnosed breast cancer cases during period of 2017 and 2018 among women records of attendees to women health center in AL-ELWYIA maternity teaching hospital. Results: the mean age at presentation was 50.8 years ,patients under age of 40 years constitute 18.9% and those between 50-59 years constitute 29.5% ,about 69.7% of the patients had more than two children , 72% of patients were married and 14.8% of patients were nulliparous ,history of lactation was recorded in 75.8% of patients, family history of cancer was positive in 23.5% of patients , clinically the most common presenting symptom was breast lumps 68.9% of patients followed by skin changes 13.6% of patients, skin ulceration 1.1% of patients, bloody nipple discharge 6.8% of patients, bilateral breast involvement was encountered in 1.5% of patients,8.7% of patients had palpable axillary lymph nodes ,82.6% of patients had invasive ductal carcinoma followed by 12.9% of patients had lobular carcinoma and 81.8% of patients presented with grade II cancer. Conclusion: a considerable proportion of breast cancer patients in Iraq still present with locally advanced disease at the time of diagnosis that justifies the necessity to promote public awareness educational campaigns to strengthen our national early detection program.